Derivados sulfonamídicos do LASSBio-448 relaxam a traqueia de cobaia com inflamação pulmonar alérgica crônica: papel das vias do óxido nítrico e das ciclo-oxigenases na ação relaxante do LASSBio-1611 - Silva, Maria da Conceição Correia (2019)
Asthma is a chronic and multifactorial inflammatory disease of the respiratory system, characterized by bronchial remodeling and hyperresponsiveness, with treatment aimed to preventing symptoms and acute attacks. Thus, it is still necessary to improve molecules testing in animal models such as chronic allergic pulmonary inflammation (IPAC) induced by ovalbumin focusing a more effective treatment. For this, it was evaluated a possible relaxant effect of LASSBio-448 and 12 derivatives, as well as well it was investigated the mechanism of action of the most potent LASSBio in guinea pig trachea from control (GC) and IPAC (GIPAC) groups. The experimental procedures were approved by Ethic Comission on Animal Use of UFPB (protocol Nº 018/2015). LASSBio-448 relaxed trachea in both the presence and presence of epithelium of GIPAC. As showed by the prototype, the N-methylsulfonamide LASSBios (-1610, -1630, -1631, -1628, -1612 e -1623) and sulfonamidic LASSBios (-1622, -1613, -1722, -1629, -1625 e -1611) also relaxed trachea in both the presence and absence of epithelium, carbachol-contracted, from GC and GIPAC, being LASSBio-1611 the most potent of all when compared to LASSBio-448, in the absence of epithelium, in both GC (1,380-fold) and GIPAC (575-fold). Thus, it was decided to investigate its mechanism of relaxant action in trachea denuded of epithelium from GIPAC. Considering that the airway relaxation has the participation of nitric oxide (NO), it was decided to evaluate whether the NO synthase (NOS)/soluble guanylyl cyclase (sGC)/protein kinase G (PKG) would be activated by this derivative. The relaxant potency of LASSBio-1611 was reduced in the presence of L-NAME, ODQ and Rp-8-Br-PET-cGMPS, inhibitors of NOS, sGC and PKG, by approximately 170-, 155- and 195-fold, respectively. In addition, the inhibitory effect of L-NAME on the relaxing effect of LASSBio-1611 was reversed in the presence of L-arginine, the NOS substrate. These results provide strong evidence that this derivative activates this signaling pathway to relax denuded guinea pig trachea with IPAC. As the K+ and voltage-sensitive Ca2+ channels are targets of PKG, the inhibitory effect of LASSBio-1611 was tested on contractions induced by 18 or 60 mM KCl, observing an equipotency, suggesting a possible blockage of Ca2+ influx. This blockade was confirmed since the cumulative concentration-response curve to CaCl2 was paralleled shifted to the right with reduction of Emax in the presence of different concentrations of LASSBio-1611. There is evidence of an interconnection between the NOS and the ciclooxygenases (COXs) pathways, and it was observed that in the presence of indomethacin, an inhibitor of COXs, and indomentacin + L-NAME, the relaxing potency of LASSBio-1611 was considerably reduced 813- and 537-fold, respectively, indicating that there is modulation of COX, increasing the production of relaxant prostanoids in the airways. In addition, it was observed that, in silico, LASSBio-1611 has an enthalpy of formation of the ligand-macromolecule complex increased for the iNOS, nNOS, PKG, CaV1.2 and COX-2, compared to the enthalpy of standards activators and/or inhibitors. Besides, the LASSBio-1611 follows the Lipinski's rule as well as exhibits essential pharmacokinetic characteristics for a good drug candidate. Therefore, in general, all LASSBios relax guinea pig trachea of both GC and GIPAC, and that the relaxant mechanism of action of LASSBio-1611 in the GIPAC, denuded epithelium, is dependent on the NOS/sGC/PKG and COXs pathways. This increased relaxant potency of LASSBio-1611 is due to the insertion of the 1-naphthyl substituent into the sulfonamide function, increasing its lipophilicity.